Gambaran Kualitas Tidur Pada Pekerja Bergilir Di Rumah Sakit S.K. Lerik Kota Kupang Tahun 2018 - Mesa, Ericson; Manurung, Imelda F. E.; Wahyuni, Maria Magdalena Dwi (Faculty of Public Health, Nusa Cendana University, 2019)
Sleep is a basic human need. Sleep can help maintain the balance of both physiologically and psychologically to maintain health and life. However, the process is hampered sleep can cause people to experience a lack of sleep and consequently people will get tired and decreased concentration. This resulted in a decrease in work productivity and can cause accidents. The purpose of this study is to describe the quality of sleep in rotating workers at SK Lerik Hospital Kupang City in 2018. The research was conducted at the Hospital of SK Lerik starting in May-June 2018. This study is a quantitative study with a descriptive survey method. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). The total sample in this study amounted to 126 people. The results showed that 114 (90,48%) of respondents have poor sleep quality, 77 (61,11%) of respondents considered that the quality of sleep is good, 45 (35,71%) of respondents have very less sleep latency, 53 (42,06%) of respondents slept 5-6 hours per day, 47 (37,30%) had sleep inefficient, 90 (71,43%) of respondents experiencing mild sleep disturbances, 118 (93,65%) of respondents never use sleeping pills, and 61 (48,41%) of respondents considered that the dysfunction experienced sleep during the day only a minor problem, In order to have a good quality sleep, should reduce the habit of using electronic devices (Smartphone and TV) before sleep and workers take turns at night should make up for lack of sleep at night with a nap sufficient.